Analisis aktivitas belajar bahasa Indonesia tema 5 di rumah selama pandemi covid-19 peserta didik kelas IV sekolah dasar - Leny Karismawati; Sukarno Sukarno; Muhammad Ismail Sriyanto (Didaktika Dwija Indria, 2021)
Activities carried out between individuals and individuals with an environtment that will bring good change. Learning activities are very influential on the learning outcomes of students. The purpose of this study was to analyze the learning activities of fourth grade students in the subject of Indonesian language theme 5 Elementary School of Pajang 4 Surakarta.This research uses qualitative research with a case study method. The activities studied were visual activities, speaking activities, listening activities, writing activities,and motor activities carried out during learning at home. This research subjects were teachers and all of fourth grade students. Data obtained from questionnaire sheets, interviews, and documentation. The results of visual activities were in the the medium category with total 16 students. The indicators speaking activities in the medium category with total 12  students. For the medium category of listening activities, the number of students is 17 students. The indicator for writing activity in the medium category with 17 students. And the last is high category is for motor activity with total 16 students.